Strategi Investasi & Manajemen Resiko Rumah Sakit Swasta di Bali - Ni Ketut Yunita Wulan Dewi; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study is to understand the investment policies of financial aspects based on risk management and to know that the investment studies are appropriate. This study uses qualitative methods that explore the implementation of risk management-based investment policies at Denpasar private hospital. Data collection uses documentation techniques and in-depth interviews with the board of directors and hospital finance staff. The data is then analyzed qualitatively by data reduction, data presentation, and conclusion drawing.            The results of the calculation using the NPV method obtained a positive value of Rp. 463.592.397, the IRR method obtained an interest rate of 10,62% and the PP method shows the return on investment within 8 years so the project is said to be feasible. Regarding investment risks, hospitals have not implemented an optimal risk management process so that it has the potential to pose a risk of loss.            The application of risk management to investment policies is important even though these investments are feasible, especially related to the development of risk mitigation strategies. This study discusses the analysis of hospital investment policy from the financial aspect, so it is expected that further research add other aspects as a reference in assessing investment feasibility.